2023
DOI: 10.1038/s41598-023-31743-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive flexibility in moderating the effect of school-related stress exposure

Abstract: Educators are exposed to various stressful events as part of their ongoing work, including violence, sexual assaults, suicidal behavior, and loss or illness of students or their family members. Previous studies revealed an increased risk of developing PTSD symptoms in healthcare and supportive professionals exposed to repeated stress as part of their work. Cognitive flexibility might be a protective factor against the negative effect of such stress. The current study aimed to examine the interactive effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Educators are frequently exposed to school-related stress that may impair their functioning and well-being 14 , 40 , 52 . The current study aimed to test the effect of internal (regulatory flexibility) and external (school climate) resources on the relationship between school-related stress and the tendency to develop depressive symptoms in this population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Educators are frequently exposed to school-related stress that may impair their functioning and well-being 14 , 40 , 52 . The current study aimed to test the effect of internal (regulatory flexibility) and external (school climate) resources on the relationship between school-related stress and the tendency to develop depressive symptoms in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated exposure to school-related stress 40 , 46 , 47 is a 10-item questionnaire that assesses the frequency of exposure to common school-related stressful incidents in an average month. The respondents were asked to rate their exposure frequency to each incident on a scale from 1 (not at all) to 6 (at least a few times a week).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the appropriate sample size, a statistical power analysis was performed based on a medium effect size (Cohen's f = 0.25), which is frequently employed in previous research (Cohen, 1988;Harel et al, 2023;Huang et al, 2023;Zhao et al, 2022). The results suggested that a sample size of 54 participants was deemed necessary to detect the hypothesized effect at α = .05 and β = .95 (Faul et al, 2007).…”
Section: Participantsmentioning
confidence: 99%